Dialog Profetis Untuk Misi Sedunia: Perspektif Seorang Non Misionaris - Ignas Kleden (Perspektif, 2008)
This essay deals with three contemporary world phenomena and the interplay between them. Those are prophetic dialog, the new concept of missionary work as the missio Dei, and the globalized world as a context where both prophetic dialog and God's mission are to take place. Prophetic dialog and the missio Dei emphasize the primacy of God's initiative, in which the Christians in general and the missionaries in particular are involved as mere partici- pants. The concept of prophetic dialog brings into relief social groups that become the main partners in the dialog. The concept of missio Dei is under- pinned by the notion of the Kingdom of God in the present ecclesiology. Kingdom of God is supposed to be larger, more fundamental, and more deep- going than the Church. There are therefore universal Catholic Church and a global world in which the church is to work. This essay tries to show that there is a common denominator between the religious social movement as a driving force of globalization and the missionary work though they aim at different goals. Whereas globalization might lead to a world market and world life style, the missionary work aims to unite all nations in the Kingdom of God.